Loan guarantees, bank lending and credit risk reallocation - Carlo Altavilla; Andrew Ellul; Marco Pagano; Andrea Polo; Thomas Vlassopoulos (Goethe University Frankfurt, Center for Financial Studies (CFS), 2021)
We investigate whether government credit guarantee schemes, extensively used at the onset of the Covid-19 pandemic, led to substitution of non-guaranteed with guaranteed credit rather than fully adding to the supply of lending. We study this issue using a unique euro-area credit register data, matched with supervisory bank data, and establish two main findings. First, guaranteed loans were mostly extended to small but comparatively creditworthy firms in sectors severely affected by the pandemic, borrowing from large, liquid and well-capitalized banks. Second, guaranteed loans partially substitute pre-existing non-guaranteed debt. For firms borrowing from multiple banks, the substitution mainly arises from the lending behavior of the bank extending guaranteed loans. Substitution was highest for funding granted to riskier and smaller firms in sectors more affected by the pandemic, and borrowing from larger and stronger banks. Overall, the evidence indicates that government guarantees contributed to the continued extension of credit to relatively creditworthy firms hit by the pandemic, but also benefited banks' balance sheets to some extent.
Keywords: G18; G21; E63; H12; H81; 330; loan guarantees; bank lending; COVID-19 pandemic; substitution; credit risk